Model Permainan Air “Swimming Couple With Pull Buoy” Untuk Meningkatkan Kecepatan Renang Gaya Bebas - Intan Rizka Ginting; Harwanto Harwanto; Lukmanul Hakim (MENDIDIK: Jurnal Kajian Pendidikan dan Pengajaran, 2020)
Swimming Couple With Pull Buoy is a new model of water games at one of the water clubs in Mojokerto Orcanala. The purpose of this study was to develop a swimming partner with a pull buoy and to describe the effectiveness of the water swimming couple game model with the pull buoy in increasing the speed of freestyle swimming. This research is a development research. The subject is Club Orcanala Aquatic Mojokerto. The methods used were questionnaires and tests. The instruments used were the learning model validation questionnaire, response questionnaire, and performance test. The results showed that the swimming pair with the pull buoy was valid according to the validation results, positive user responses, and the water swimming couple game model with the pull buoy was effective in increasing the speed of the freestyle swimming